Facebook Groups as a Means of Income During the Pandemic - Aris Munandar, Maryadi; Soegoto, Herman (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2022)
This study aims to determine the extent of the potential of the Facebook group as a means of income during the pandemic. The effects of the pandemic have forced people to work from home. Some professions don’t allow working from home, so people’s incomes decrease. Starting from people’s habit who mostly always use social media, researchers propose Facebook as the main focus of alternative income sources. Researchers use qualitative methods which include problem analysis, data collection to data analysis that makes it easier for researchers to understand deeply the problems that exist in society. Facebook groups are very effective for increasing the income. All the features in the Facebook group can be used as an online business opportunity, so with the right guidance and direction, it is hoped that it can become an online business opportunity option and eventually can become a new source of income for the Society arround Desa Sumber Jaya, Kabupaten Bekasi